MATERIALS TO FUNGAL FLORA CONTAMINATING SPICES (Proceedings of the YSU B: Chemical and Biological Sciences, 2010)
In this article is reported about fungal species contaminating spices: red pepper, black pepper, suneli, carry. Data about 29 species of fungi contaminating spices are given. Isolated species belong to Zygomycetes and Deuteromycetes classes. 21 species belong to Moniliaceae family.
Keywords: fungal species; pepper; suneli; carry